Library and Research Leadership Roundtable-Transformative Agreements: Successes, Challenges, and Lessons Learned - Matizirofa, Lazarus Gallant (University of the Witwatersrand, Johannesburg, 2025)
Abstract not available
A webinar presentation by Lazarus Gallant Matizirofa, presented at the Library and Research Leadership Roundtable hosted by Elsevier on 24 March 2025
Keywords: Scholarly publishing; Transformative Agreements; Lessons learned; Transformative Agreements challenges; Transformative Agreements successes; Open Access Publishing; University of the Witwatersrand; SDG-10: Reduced inequalities; SDG-17: Partnerships for the goals